Pit-embellished low-valent metal active sites customize CO2 photoreduction to methanol. Issue 1 (11th November 2022) - Zhao, Wei; Ding, Miao; Yang, Pengxin; Wang, Qiang; Zhang, Kaifu; Zhan, Xiaowen; Yu, Yu; Luo, Qiquan; Gao, Shan; Yang, Jinlong; Xie, Yi
Abstract : Controllable adjustment of low-valent metal active sites near the pits can promote the WO3− x surface charge delocalization, which dominates the formation of *CHO intermediates, thus customizing a unique reaction pathway for CO2 reduction to CH3 OH. Abstract : Customizing catalytic reaction pathways by precisely designing the metal active sites and electron–hole separated channels of metal oxides to simultaneously achieve a high yield and selectivity of photocatalytic CO2 reduction to liquid fuel remains a challenge. Herein, we for the first time propose that low-valent tungsten sites favor the formation of key CHO* intermediates for highly selective photocatalytic reduction of CO2 to CH3 OH. In situ spectroscopic results and DFT calculations demonstrate that coordinately unsaturated low-valent W sites near the tungsten trioxide (denoted WO3− x ) pits serve as catalytic sites and electron capture sites enabling the adsorbed CO2 to selectively form a predominant lower-energy *CHO intermediate instead of *CO, thereby triggering a unique reaction pathway for CO2 reduction to CH3 OH. Accordingly, the optimal WO3− x delivers a notable CH3 OH selectivity of up to 86% with a high evolution rate of 17 μmol g −1 h −1 under sunlight irradiation. This work highlights how low-valent metal active sites in the surface pits can be controlled at the atomic-level to customize the CO2 reduction reaction (CO2 RR) pathway to generate valuable liquid fuels.